Analisis Makna dan Fungsi Mantra Tri Sandya Dalam Tradisi Hindu Desa Karang Sari Kecamatan Pakuan Ratu Kabupaten Way Kanan - Sutisna, I Made Aris; Armariena, Dian Nuzulia; Hetilaniar, Hetilaniar (Indonesian Research Journal on Education, 2022)
This research aims to describe the Analysis of the Meaning and Function of the Tri Sandya Mantrain the Hindu Tradition of Karang Sari Village, Pakuan Ratu District, Way Kanan Regency. Theresearch method used is the qualitative descriptive method. Data collection techniques using observation, interviews, and recording. The data analysis technique in this research is contentanalysis. Based on data analysis conducted on 16 Trisandya mantras studied, there are selfprotection mantras, safety mantras, health mantras, headache mantras, and bridal safety mantras. The function of the Trisandya mantra is to protect ourselves. While the meaning of this Trisandya mantra, namely worshiping ancestors to ask for self-protection such as when traveling to be safe on the road, headache mantras mean to cure and eliminate headaches in people, and bridal safety mantras to provide smoothness so that there are no obstacles during the wedding event.